Tip60: Main Functions and Its Inhibitors - Zhang, Xiaoli; Wu, Jiyong; Luan, Yepeng (Mini Reviews in Medicinal Chemistry, 2017)
Background: Tip60, the founding member of MYST histone acetyltransferase family, was originally identified as a cellular acetyltransferase protein that interacts with HIV-1 Tat. Tip60 plays roles in many processes such as cellular signaling transmission, DNA damage repair, cell cycle and checkpoint control and apoptosis by acetylating its histone or non-histone substrates. Results: Dysfunction of Tip60 could promote or suppress diseases including different kinds of cancers. Conclusion: Here, main functions and its known inhibitors were summarized. >
Keywords: Tip60